Electrochemical Dearomatizing Spirolactonization and Spiroetherification of Naphthols and Phenols - Sarvi Beigbaghlou, Somayyeh; Yafele, Robert S.; Kalek, Marcin (Synthesis, 2023)
An electrochemical oxidative ortho-dearomatization of naphthols and phenols with an intramolecular C–O bond formation has been developed. A careful optimization of the reaction parameters allowed for the application of free phenols as the starting materials, in contrast to the existing alternative procedures necessitating aryl methyl ether substrates. The reaction delivers an array of spirolactones and spiroethers in yields up to 97%, under simple experimental conditions: in a constant current mode, using an undivided cell, and without an inert atmosphere. The method avoids using catalysts or stoichiometric oxidants (e.g., hypervalent iodine reagents), generating hydrogen as the sole byproduct.
Keywords: electrosynthesis; dearomatization; oxidation; spirolactonization; spiroetherification; naphthols; phenols